Model Pengukuran Produktivitas Berdasarkan Pendekatan Rasio Output Per Input - Sarjono, Haryadi (Journal the Winners: Economics, Business, Management, and Information System Journal, 2001)
Objective of this research is to find model which measure productivity. That measuring uses a ratio between effectivity of goal achievement as the certain quality level (output) and efficiency application of available source (input). It is concluded that (1) to increase productivity input and output are variable which must be controlled; (2) Increasing productivity can increase competitive power of a company and also can a help a company to have a new investment.